Enhancing Job Satisfaction through Human Resource Information Systems and Communication: A Commitment-Based Approach to Achieve Sustainable Development Goals (SDGs) in Education-Oriented Organizations - Imaniyati, Nani; Ratnasari, Cindy Diana; Adman, A. (ASEAN Journal of Educational Research and Technology, 2025)
This study examines the influence of Human Resource Information Systems (HRIS) and organizational communication on job satisfaction, with organizational commitment serving as a mediating factor in the educational context. A quantitative method was employed through a structured survey involving employees in an education-related industrial organization. The analysis was conducted using SPSS to test direct and indirect relationships among variables. The results indicate that both HRIS and communication significantly enhance job satisfaction, and this effect is further strengthened when organizational commitment is present. Because HRIS improves transparency and communication fosters engagement, employees feel more aligned with organizational goals, increasing satisfaction. These findings provide insights for educational institutions and human resource managers seeking to implement data-driven and participatory systems in line with SDG 8, which promotes decent work and economic growth through inclusive workplace strategies.